2015
DOI: 10.1097/ede.0000000000000339
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report

Abstract: Background Few previous studies have investigated the association between the severity of an infectious disease and the length of incubation period. Methods We estimated the association between the length of the incubation period and the severity of infection with the severe acute respiratory syndrome (SARS) coronavirus, using data from the epidemic in 2003 in Hong Kong. Results We estimated the incubation period of SARS based on a subset of patients with available data on exposure periods and a separate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 15 publications
(30 reference statements)
5
31
0
Order By: Relevance
“…We estimated the incubation period of MERS-CoV cases during the recent MERS outbreak in South Korea and found that patients who died had a shorter incubation period than patients who survived. In a previous study, we found that the length of incubation period in patients infected with SARS coronavirus was also correlated with severity of the disease, with a shorter incubation period for patients who died (9). The pathogenesis of MERS-CoV and SARS coronavirus infection is similar (11), with a rapid progression to respiratory failure and intubation occurring ≈1 week after onset of symptoms and up to 5 days earlier in MERS patients than in SARS patients (4,12).…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…We estimated the incubation period of MERS-CoV cases during the recent MERS outbreak in South Korea and found that patients who died had a shorter incubation period than patients who survived. In a previous study, we found that the length of incubation period in patients infected with SARS coronavirus was also correlated with severity of the disease, with a shorter incubation period for patients who died (9). The pathogenesis of MERS-CoV and SARS coronavirus infection is similar (11), with a rapid progression to respiratory failure and intubation occurring ≈1 week after onset of symptoms and up to 5 days earlier in MERS patients than in SARS patients (4,12).…”
Section: Discussionmentioning
confidence: 82%
“…For most cases, information on exposure was recorded as intervals >2 days during which infection was believed to have occurred, rather than exact dates of presumed infection. For the subset of patients without available exposure data, we assumed that their incubation time was 0-21 days because 21 days was the longest incubation period reported (9,10). Data for patients is provided in online Technical Appendix 1 (http://wwwnc.cdc.gov/EID/article/22/3/ 15-1437-Techapp1.xlsx).…”
Section: The Studymentioning
confidence: 99%
See 3 more Smart Citations